1996
DOI: 10.1088/0954-3899/22/10/013
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic rays in the Magellanic clouds

Abstract: EGRET data from the Compton Gamma Ray Observatory have been used to determine the flux of gamma rays from the Small Magellanic Cloud (SMC). When compared with data at other wavelengths it is found that the parents of the gamma rays, the initiating cosmic rays (CRs), are concentrated much more strongly than is the case for the Large Magellanic Cloud (LMC). A consequence is that unless a single discrete gamma-ray source is responsible, the efficiency of CR production and/or trapping in the SMC is higher than wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…If we assume that the same processes occur in the SMC, we can obtain that the -ray integral flux with energy greater than 300 MeV from the pulsars in the SMC is #8.6 10 29 cm 22 s 21 . Compared to the observed value of (2.2<0.7) 10 28 cm 22 s 21 (Al-Dargazelli et al 1996b), we obtain that the #39 per cent of the observed -rays for E P300 MeV in the LMC come from the pulsars. Therefore, we may conclude that pulsar contribution in the SMC is also very important.…”
Section: O N C Lu S I O N S a N D Discussion Scontrasting
confidence: 46%
“…If we assume that the same processes occur in the SMC, we can obtain that the -ray integral flux with energy greater than 300 MeV from the pulsars in the SMC is #8.6 10 29 cm 22 s 21 . Compared to the observed value of (2.2<0.7) 10 28 cm 22 s 21 (Al-Dargazelli et al 1996b), we obtain that the #39 per cent of the observed -rays for E P300 MeV in the LMC come from the pulsars. Therefore, we may conclude that pulsar contribution in the SMC is also very important.…”
Section: O N C Lu S I O N S a N D Discussion Scontrasting
confidence: 46%